Pengaruh media pembelajaran berbasis kelase terhadap minat belajar siswa kelas X SMAN 4 Banjarmasin - Rusmayadi, Redo; Rahmattullah, Muhammad; Nicky Gillian Ratumbuysang, Monry Fraick; Rizky, Maulana (Jurnal Pendidikan Ekonomi (JUPE), 2024)
This research aims to determine the effect of using learning media on the learning interest of class X students at SMA Negeri 4 Banjarmasin. The type of research used in this research is quantitative with descriptive quantitative type using questionnaire and documentation methods and the sample used is students in classes X-3 and X-4 with a total of 78 people. The validity test used in this research uses the validity test itself using the Product Moment (Pearson) correlation formula and uses the Cronbach Alpha reliability test. The data analysis technique used in this research is to test the prerequisites for analysis using the normality test, while for hypothesis testing using a simple regression analysis formula, and partial testing (T test). Based on the research results, it was concluded that the classroom-based learning media variable had a significant influence on students' interest in learning.